Diagnostic Cardiac Catheterization for Congenital Heart Disease in Nepal - Regmi, Shyam R; Maskey, A; Dubey, L; Malla, R; Bhatt, Y; Rajbhandari, R; Limbu, YR; KC, MB (Nepalese Heart Journal, 2013)
Accurate preoperative anatomic and functional diagnosis is of vital importance for surgical repair of congenital heart disease. The diagnostic accuracy of echocardiography alone in congenital heart disease is satisfactory but interventional catheterization is still required to derive the adequate information before surgical repair. This is a retrospective review of our early results with cardiac catheterization for congenital heart disease in Shahid Gangalal National Heart Center (SGNHC), Nepal. Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 5-7 DOI: http://dx.doi.org/10.3126/njh.v7i1.8494